Chemoselective Electrochemical Cleavage of Sulfonimides as a Direct Way to Sulfonamides - Salvadori, Karolína; Churý, Michal; Budka, Jan; Harvalík, Jakub; Matějka, Pavel; Šimková, Ludmila; Lhoták, Pavel (The Journal of organic chemistry, 2024)
A new method for selective cleavage of sulfonimides into sulfonamides in high yields using a simple electrochemical approach is shown. As revealed by the electrochemical study, the aromatic sulfonimides can be selectively cleaved by electrolysis of the starting compound at a given potential (only -0.9 V vs SCE for the nosyl group). The high chemoselectivity was confirmed by preparative electrolysis, and the results were supported with DFT calculations of a set of substances bearing different sulfonimide functions. Moreover, various experimental setups together with other attempts to simplify the procedure were tested. Finally, the removal of the p-nosyl group from the corresponding sulfonimides proceeds smoothly regardless of the number of nosyl groups and the overall shape of the complex molecule. Thus, the method is interesting for use in the field of multifunctional molecules such as calix[n]arenes.